The Influence of Self-Efficacy on the Development of Entrepreneurial Intentions and Actions - Boyd, Nancy G.; Vozikis, George S. (Entrepreneurship Theory and Practice, 1994)
The contextual factors of entrepreneurship consist of social, political, and economic variables such as displacement, changes in markets, and government deregulation (Bird, 1988). Entrepreneurial intentions are further structured by both rational/analytic thinking (goal-directed behavior) and intuitive/holistic thinking (vision). These thought processes underlie the creation of formal business plans, opportunity analysis, and other goal-directed behavior. This paper further develops Bird's model of entrepreneurial intentionality by suggesting that individual self-efficacy, which has been defined as a person's belief in his or her capability to perform a task, influences the development of both entrepreneurial intentions and actions or behaviors.